How working capital management affects the profitability of small and medium size enterprises (SMES) in Malaysia? - M. T., Hirnissa; Mohd Ashhari, Zariyawati (Alicon Publications, 2017)
The purpose of this study is to investigate the effect of working capital management on the profitability of small and medium enterprises (SMEs). Balanced panel data analysis is used to achieve the purpose. The research sample consists of 722 firm-year of SMEs operated in Malaysia from 2011 to 2013. Finding reveals net working capital is positively associated with the return on assets. Besides, the component of net working capital also has positively related with return on asset. This suggests that SMEs can increase their profit when they increase the investment in working capital management. SMEs should invest more in inventories to avoid inventories shortage especially when having immediate demand from the customer. The longer of a length to pay creditor also provide SMEs more cash to use to buy inventories to accomplish demand of customers, which consequently increase the profit of the SMEs.